2010
DOI: 10.1111/j.1742-1241.2010.02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the once-daily levofloxacin-containing triple therapy with the twice-daily standard triple therapy for first-lineHelicobacter pylorieradication: a prospective randomised study

Abstract: The efficacy and tolerability of once-daily levofloxacin-containing triple therapy are equal to those of the standard twice-daily triple therapy in this study. However, none of the treatment regimens evaluated achieved enough eradication efficacies to be considered as a recommendable first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Chen et al (35) emphasized that efficacy and tolerability of once-daily and twice-daily triple therapy (levofloxacin 500 mg, esomeprazole 40 mg and clarithromycin 500 mg) were equal; however, none of the regimens was effective enough to be considered as a recommendable first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (35) emphasized that efficacy and tolerability of once-daily and twice-daily triple therapy (levofloxacin 500 mg, esomeprazole 40 mg and clarithromycin 500 mg) were equal; however, none of the regimens was effective enough to be considered as a recommendable first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the rapid increase of antibiotic resistance, the most commonly recommended regimen led to an unacceptably low success rate for the treatment (Table .). Zheng et al.…”
Section: Eradication Of H Pylori Infectionmentioning
confidence: 99%
“…Studies demonstrated that increasing the dosage of levofloxacin cannot overcome levofloxacin resistance [38, 39]. Furthermore, previous studies suggest that once-daily dosing of a levofloxacin-based triple regimen may be as efficacious as twice daily [40]. …”
Section: Quinolone-based Therapymentioning
confidence: 99%